STUDI TERHADAP TINDAKAN PENYIDIK DALAM MENANGANI SINDIKAT PENADAHAN ATAS OBJEK JAMINAN HASIL TRANSAKSI FIDUSIA DI POLRESTA MALANG - Wardoyo, Yohana Puspitasari; Afandi, Fery Kusnaini (Faculty of Law, University of Muhammadiyah Malang, 2019)
The criminal act of unconscious fiduciary collateral is often experienced by many people, various modes of operation are also carried out. This has become a common secret for law enforcers, especially the police who receive reports too often of alleged criminal offenses. As for the formulation of the problems are: 1) What are the actions of the Investigator to uncover the Penal syndicate for the object resulting from the Fiduciary collateral transaction; and 2) What are the Obstacles of Investigators in handling criminal acts of overcoming objects of fiduciary collateral transaction results. The approach in this study uses a mixed approach, there are conceptual approach and sociological approach. The results of the study: that in carrying out law enforcement criminal acts fiduciary collateral objects in the Malang City Resort Police are very weak, it needs special handling to eradicate criminal offenses that often occur by syndicates or certain groups.